Caring Hearts Coupled with Helping Hands: Making a Difference for Children with Medical Hair Loss. Issue 4 (July 2017) - Callister, Lynn Clark
Abstract : Medical hair loss can be devastating to children and adolescents. Dr. Callister highlights three nonprofit organizations that provide wigs for children with medical hair loss.